2020
DOI: 10.1002/aenm.202000197
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Perovskite Solar Cells by Reducing Interface‐Mediated Recombination: a Bulky Amine Approach

Abstract: meantime, the ease of the solution process at low temperature renders this technology up-and-coming for large-scale low-cost manufacture. However, these solution-processed perovskite films are usually polycrystalline, which readily form defects at the grain boundaries and on the surface of the films. [1][2][3][4][5][6] Such defects are the center of non-radiative recombination of photo-generated electrons and holes, which causes shorter carrier lifetime and lower open-circuit voltage (V OC ). Hence, in real de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
208
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 78 publications
(111 reference statements)
5
208
0
Order By: Relevance
“…[ 8–12 ] In order to further improve the stability and efficiency of PSCs, it is necessary to select appropriate passivators to modify the interface of the PVSK layer. [ 13–16 ] In the past few years, numerous studies have demonstrated that functional groups, such as pyridine, thiophene, iodopentafluorobenzene, [ 17 ] cyano, [ 18 ] sulfonate (OSO 3 − ), [ 19 ] fluorine, carboxylic acid could act as the passivator of defects in perovskite film, for example, under‐coordinated Pb 2+ cations, and hence reduce the nonradiative charge recombination. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–12 ] In order to further improve the stability and efficiency of PSCs, it is necessary to select appropriate passivators to modify the interface of the PVSK layer. [ 13–16 ] In the past few years, numerous studies have demonstrated that functional groups, such as pyridine, thiophene, iodopentafluorobenzene, [ 17 ] cyano, [ 18 ] sulfonate (OSO 3 − ), [ 19 ] fluorine, carboxylic acid could act as the passivator of defects in perovskite film, for example, under‐coordinated Pb 2+ cations, and hence reduce the nonradiative charge recombination. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The Nyquist plots obtained from EIS measurement at a bias of 0.8 V exhibit two semicircles, as shown in Figure 6b. According to the equivalent circuit model (inset), R rec is the sum of the resistance of the first semicircle at high frequency and the second semicircle at low frequency [73,74] . Obviously, the diameters of two semicircles of the K5 device are larger than that of the Control device, indicating larger R rec and reduced interface non‐radiative recombination.…”
Section: Resultsmentioning
confidence: 99%
“…According to group II , the surface morphology of perovskite films tested by high temperature environment changed compared with group I , and many white particles appeared on the surface, which has been proved to be PbI 2 . [ 33 ] The MABr and GABr films, on the other hand, seemed to show better crystal quality and smoother film surfaces. XRD results are consistent with the SEM, indicating that surface passivation of MABr and GABr can improve the thermal stability of perovskite films.…”
Section: Resultsmentioning
confidence: 99%